Recent landslide studies in the Dolomites (Eastern Italian Alps) for hazard assessment and mitigation - Maotovani, F.; Pasuto, A.; Silvaoo, S. (Journal of Nepal Geological Society, 2000)
The correct interpretation of landslide hazard, and consequently the optimisation of the interventions to be carried out in order to mitigate the loss of human lives and economic assets, depends on some general considerations. Firstly, gravitational phenomena should be regarded as an effect of natural landscape evolution, and secondly, the interaction of these phenomena with human activities and structures causes casualties and damage. Indeed, the population growth has led to greater needs for space and natural resources. On the other hand, the constant technological progress and improvement of living standards have caused remarkable changes in natural environment. Consequently, the events such as landslides have had increasingly serious consequences on human life and activities. The Eastern Italian Alps, and in particular the Dolomites, are famous mountainous areas for their well-organised winter and summer resorts located at different elevations along the slopes and in the valleys. The territory includes high (more than 3,000 m) peaks alternating with densely populated valleys. Most of the villages are located on alluvial fans, at the bottom of the valley, or on the toe of ancient landslide accumulations. This fact implies a high degree of risk for civil populations, urban settlements, and infrastructure. The Dolomites are prone to sliding owing to their steeps lopes and unfavourable structural setting (i.e. an intensely faulted and jointed sequence of rigid and plastic formations). In this framework, the paper describes some experience of landslide investigations and monitoring carried out in this area.